Determinants of Access to Healthcare: A Survey in Istanbul - Muhammed Ziya Paköz; Mehmet Ali Yüzer (European Regional Science Association (ERSA), 2014)
Access to healthcare is formed according to the characteristics of the supply and demand. While siting hospitals, ?equity' in access to healthcare should be taken as a basis for all segments of society, and necessary measures should be taken to ensure that vulnerable groups benefit from health services adequately. This necessitates evaluating spatial and non-spatial dimensions of access to healthcare together. Spatial dimension emphasizes importance of the distance whereas non-spatial dimension includes factors such as level of income, educational attainment level, culture, ethnicity, age and sex. In this paper, results of the survey conducted on 756 households in Istanbul were put to evaluation within the framework of the dimensions of the access to healthcare; spatial patterns of the access to inpatient services in Istanbul were examined over the survey results. Dimensions of the access to healthcare put forward the level of access as well. Results of the survey show that different dimensions of the access to healthcare are effective with various degrees in hospital choices. However, as the level of income changes, so does the hospital preferences. Middle and low income groups have more limited budget for healthcare services and ownership of personal car is less frequent, so demand elasticity is lower compared to the high and high-middle income groups. Therefore, ?accessibility' and ?affordability' dimensions of the access come to the fore for middle and low income groups while ?acceptability' is cared more by the high and high-middle income groups. The paper also deals with the relationship between supply characteristics and travel time / travel distance accepted and realized for going to hospital in Istanbul. According to the international practices and literature, the maximum travel time for access to hospital is accepted generally as ?30 minutes', which turns out to be parallel with the survey results. However, the realized travel distance differentiates based on the type (public, private) and nature (regional-local) of the hospital. Distance covered for regional hospitals (training and research hospitals and university hospitals) and travel rate outside the district are higher than the distance covered for local hospitals. Similarly, distance covered for private hospitals is more than the distance made for public hospitals. The paper not only evaluates the spatial and non-spatial factors together, but also considers health supply in various aspects, reveals user behaviors which change depending on the type of the supply and the characteristics and the pattern of the city, and defines distance thresholds and border-crossing according to these features.
Keywords: I11; I14; 330; Access to healthcare; affordability; spatial accessibility; distance; Istanbul